Large vestibular schwannomas: long-term outcomes after stereotactic radiosurgery - Stastna, Daniela; Urgosik, Dusan; Chytka, Tomas; Liscak, Roman (Neuro endocrinology letters, 2021)
OBJECTIVES: Stereotactic radiosurgery (SRS) is an established treatment option of small/medium-sized vestibular schwannomas (VSs). Concerning management of the large VSs, primary SRS remains a controversial option. Our retrospective study analyzes long-term radiological and clinical outcomes of SRS in large VSs. MATERIAL AND METHODS: We retrospectively analyzed 73 patients with single large VS, treated with SRS. Inclusion criteria were: tumor volume >4 cm3, follow-up >2 years, radiological (3D-volumetric studies) and clinical follow-up. SRS was either primary (94.5%) or secondary (5.5%) treatment. The median marginal dose (50%-isodose line) was 12Gy (11.5-12Gy). Fisher exact test, t-test, ANOVA, Kaplan-Meier and Cox regression models were performed when appropriate RESULTS: The median follow-up was 5.5 years. The median VS volume at SRS was 6.5 cm3 (range 4-14.2 cm3). The tumor control rates assessed from Kaplan-Meier curve were 88.3%, 82.4% and 74.7% 5.8 and 10 years after SRS, respectively. Tumor shrinkage was observed in 83.6% of patients (n=61), unchanged volume in 4.1% patients (n=3) and progression in 12.3% (n=9). The median tumor volume significantly decreased to 4.0 cm3, measured at 5-year follow-up (p<0.0001). Large cystic VSs responded better to SRS then homogeneous. Pre-SRS serviceable hearing was present in 37% of patients; 55% of these had hearing preserved after treatment. After SRS, new facial palsy (House-Brackmann gr. III-VI) appeared in 4.1% of patients; 9.6% of patients had transient brainstem/cranial nerves edema. For tumor progression, 8.2% of patients underwent resection, 2.8% of patients repeated SRS. CONCLUSION: Our results are showing that SRS might be safe and effective primary treatment even in large VSs. However, long-term tumor control rates are lower in comparison with small/medium-sized VSs. Thus, closer follow-up should be applied.
Keywords: radiochirurgie; tumor burden; vestibulární schwannom; lidé; retrospektivní studie; Radiosurgery; Tumor Burden; výsledek terapie; Follow-Up Studies; Retrospective Studies; Treatment Outcome; následné studie; Neuroma, Acoustic; Humans